NUMERICAL ESTIMATION OF SEISMIC FRAGILITY CURVES FAMILY FOR CONFINED MASONRY BUILDINGS USING GAUSSIAN PROCESS REGRESSION WITH VERTICAL DIAGONAL STRUT MODEL APPROACH - Roy Peterson Kaputing, Alrend
Confined masonry (CM) buildings are one of the most widely used construction types in Indonesia, particularly in residential buildings. This study aims to develop a family of seismic fragility curves that can represent the potential damage of confined masonry buildings due to earthquakes. To achieve this goal, the Vertical Diagonal Strut Model (VDSM) approach is used to represent the contribution of confined masonry walls as structural elements within the building. In this study, nine structural models with various combinations of column spacing (s) and the number of stories (n) were analyzed using numerical simulations. The simulations were conducted through nonlinear time history analysis (NLTHA) utilizing Multi Stripe Analysis (MSA) to evaluate the building's performance under seismic events. The data obtained from these simulations were then used to build a Gaussian Process Regression (GPR) model, which can predict the fragility curves with a high level of accuracy. The results of this study indicate that increasing the column spacing (s) and the number of stories (n) tends to increase the seismic fragility of confined masonry buildings. The GPR approach successfully predicted fragility curves across various structural scenarios.